TINJAUAN YURIDIS KEDUDUKAN ANAK DALAM PERKAWINAN CAMPURAN DITINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN - Boris Brison; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Mixed marriage in Indonesia has been widely practiced in Indonesia. Marriage conducted between citizen and foreign citizen can bring legal effect to husband and wife who do the mixed marriage, both about citizenship of couples of citizen in this case married to foreigners. In civil law, it is known that man has a legal status since he was born, Article 2 of the Criminal Code provides an exception that a child still in the womb can be a legal subject if there is a desirable interest and is born alive. Man as subject of law means to have rights and obligations, as well as to children, children have authority in the status of property ownership in the household and have inheritance when the divorce arises from the marriage of both parents. With the many occurrences of mixed marriages in Indonesia, legal protection in mixed marriage and child protection in this mixed marriage should be well accommodated in Indonesian legislation.This type of research is normative legal research that focuses on the level of legal syncrosion with document studies on the position of marriage mixed children according to Law No.12 of 2006 on Citizenship, while if viewed from the nature of this research is descriptive. This study uses secondary data that is ready-made dataThe result of this research is the position of the child of mixed marriage products according to Law Number 12 Year 2006 regarding the Citizenship of the Republic of Indonesia that the child of the mixed marriage has the right to decide or to choose citizenship. The right is granted if it meets the requirements set after the age of 18 years. The provisions governing to elect citizenship to a child of mixed marriage shall be provided only to the child who is registered or registered at the Immigration Office. Factors that cause child custody in the case of divorce are in the father of foreign citizenship is the cause of divorce comes from Mother, father has more ability in financing life of child and child of its own who wants parenting is on your side.Keywords: child status, mixed marriage.